Islamic Inheritance Law, Son Preference and Fertility Behavior of Muslim Couples in Indonesia - Carranza, Eliana (2012)
This paper examines whether the son preference and fertility behavior of Muslim couples respond to the risk of inheritance expropriation by their extended family. According to traditional Islamic inheritance principles, only the son of a deceased man can exclude his male agnates from inheritance and preserve his estate within the nuclear household. The paper exploits cross-sectional and time variation in the application of the Islamic inheritance exclusion rule in Indonesia: between Muslim and non-Muslim populations affected by different legal systems, across men with different sibling sex composition, and before and after a change in Islamic law that allowed female children to exclude male relatives. The analysis finds that Muslim couples more affected by the exclusion rule exhibit stronger son preference, practice sex-differential fertility stopping, attain a higher proportion of sons, and have larger families than non-Muslims or Muslims for whom the exclusion rule is less binding.